Ophthalmological profile of patients living with HIV/AIDS - Janković-Terzić Katarina; Begić Vera; Dačić-Krnjaja Bojana (Vojnosanitetski Pregled)
Introduction. Serbia has 2.287 registered HIV positive persons. A certain number has ocular complications which are mainly the result of opportunistic infections accompanying this illness. Due to a highly stigmatizing environment for people living with HIV/AIDS in Serbia, they do not always seek doctors assistance despite the fear of losing their sight. Case report. We presented ophthalmologic status of nine HIV positive persons, all at the different phases of the illness. The decrease in the visual acuity was the first symptom which led to the diagnosis of HIV infection in two of our patients. Conclusion. Ophthalmologist has an important role in the multidisciplinary approach to patients with HIV/AIDS from introducing the diagnosis to the follow-up and the treatment of ocular complications which may accompany this chronic illness. With the active involvement of eye professionals serious consequences can be prevented, which have not only medical but also social and economic implications on the individual and the society as a whole.